Effects of Surface Sizing with Starch on Physical Strength Properties of Paper - Biricik, Yagmur; Sonmez, Sinan; Ozden, Oznur (Asian Journal of Chemistry, 2011)
The main role of the surface sizing is to increase the strength of the paper surface and to bind particles such as fiber and pigments to paper surface. For this purpose, starch, animal glue, methyl cellulose, carboxymethyl cellulose, polyvinyl alcohol and wax emulsions can be used and many resins polymers can be used for some special purposes. Among these, the starch is the most frequently used one. This study was performed to determine the changes on strength and printing properties of sulfite base paper and vegetable parchment base paper with sizing by starch having a solid content of 10 % on the K-Coater laboratory type. According to the results of paper strengths and printing tests, it has been found that surface sizing with starch improves positively paper physical strength properties and printability.